FAKTOR PENYEBAB KETIDAKPATUHAN IBU MELAKUKAN IMUNISASI DASAR DI KELURAHAN SIDEREJO HILIR - Nova Linda Rambe; Prisky Ramadhani (Jurnal Ilmiah Kebidanan Imelda, 2024)
Within the scope of health services, the preventive sector is the main priority. In the preventive sector, it is a top priority in the scope of health services. One form of health intervention that is very effective in reducing infant and toddler mortality rates in the health service system is immunization. Objective: The aim of this research is to find out the causes of maternal non-compliance with basic immunization in Siderejo Hilir Village. Method: This research uses qualitative methods as a phenomenological approach by producing in-depth information from interview scripts, interview notes and documentation. The research location in this research is located in Siderejo Hilir Village, Medan Tembung subdistrict. There were 5 participants in the research. The overall research time for this research was 3 months, starting from September 21 to December 19 2023. Results: from the results of interviews with the five participants, 100% of them had not carried out basic immunizations for their children. The majority of participants were in their 30s. The majority of participants have junior high school/equivalent education, with the mother's status working as a housewife. Factors that cause mothers' non-compliance in carrying out basic immunizations come from several sources that have been explored. The author is of the opinion that the factors that cause mothers' non-compliance in carrying out basic immunizations include: Education, Knowledge, confidence, work, economy, and family support.